Three new highly oxygenated azaphilones from an endophytic fungus Penicillium sp. LZUC-S1. (21st December 2022) - Feng, Zi-Yun; Huang, Pei-Zhi; Jiang, Song-Jie; Shen, Shi-Jin; Chen, Jian-Jun
Graphical abstract: Highlights: Three new highly oxygenated azaphilones were isolated from Penicillium sp. LZUC-S1. Compound 1 belongs to a rare class of azaphilone possessing an acetonyl at C-8. Some azaphilones showed antifungal activity against four phytopathogenic fungi. Abstract: Three new highly oxygenated azaphilones, penicilphilones A–C (1 –3 ), along with four known analogues (4 –7 ) were isolated from the culture of Penicillium sp. LZUC-S1. Their structures were elucidated by detailed spectroscopic data interpretation, electronic circular dichroism (ECD) calculation, and DP4+ analysis. 1 belongs to a rare class of azaphilone possessing an acetonyl at C-8. 2, 5, and 6 are uncommon azaphilones holding a chain with four carbons at C-8. Compounds 1, 3, and 4 showed potent activities against the selected phytopathogenic fungi with inhibitory rates ranging from 49.8 to 78.6 % at 50 μg/mL. In addition, a putative biogenetic pathway for compounds 1, 2, 5, and 6 was proposed.